A case study on effective teaching strategies for attaining course learning outcomes - Ahmed, Awwad Othman Abdelaziz; Ibrahim, Intisar Zakariya Ahmed (Linguistics and Culture Review, 2021)
Lesson planning has been a subject of debate within the realm of education, with contrasting views regarding its merits. This study employs a descriptive cross-sectional survey design to investigate lecture planning practices among teaching staff in the English Language and Translation Department at Qassim University, Saudi Arabia. The research focuses on understanding current practices and potential gender-related differences in teaching strategies. Data were collected through a structured questionnaire distributed to 26 university teaching staff, evenly split between males and females. The results indicate that faculty members exhibit a positive attitude towards lesson planning, emphasizing careful preparation, alignment with course objectives, and responsiveness to student needs. While some variations between male and female teachers were observed, particularly in lesson planning and the use of teaching aids, no significant gender-based disparities were found in many teaching practices. This suggests that effective teaching strategies can be employed by educators of any gender, challenging gender-based assumptions about teaching styles. Implications of the study underscore the importance of recognizing and celebrating diverse teaching approaches among faculty members. Rather than making gender-based assumptions, educational institutions should foster an inclusive environment where educators are encouraged to leverage their unique strengths.